2020
DOI: 10.1002/jsfa.10240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two debittering processes on the alkaloid content and quality characteristics of lupin (Lupinus mutabilis Sweet)

Abstract: BACKGROUND The presence of quinolizidine alkaloids (QAs) in the species Lupinus mutabilis Sweet limits the expansion of its consumption and use, despite its high protein content. The objective of this research was therefore to determine the effect of two thermal treatments, aqueous (ATT) and saline (STT), on the QAs and total protein content, as well as on the texture (fracturability and hardness), visual perception attributes – hue (H*), luminosity (L*) and chromatism (C*) – and grain size in three lupin vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…Cortés‐Avendaño et al (2020) reported an average total content of alkaloids equal to 0.003% db (lower than the safe limit) after an AQE of 151 hr; however, the amount of water used was not measured as they used running water for 120 hr in the washing stage. Villacrés et al (2020) used an aqueous thermal treatment (time process of 87 hr and 96 L of water) and saline heat treatment (time process of 58 hr and 66 L of water) for L. mutabilis debittering, both performed with a stirring system in the washing stage, obtaining an 80% extraction yield which is lower than the obtained in this research. It is deductible that extending the time process until getting the percentage of total alkaloids extracted for its safe consumption would have demanded greater use of water, time, and energy.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Cortés‐Avendaño et al (2020) reported an average total content of alkaloids equal to 0.003% db (lower than the safe limit) after an AQE of 151 hr; however, the amount of water used was not measured as they used running water for 120 hr in the washing stage. Villacrés et al (2020) used an aqueous thermal treatment (time process of 87 hr and 96 L of water) and saline heat treatment (time process of 58 hr and 66 L of water) for L. mutabilis debittering, both performed with a stirring system in the washing stage, obtaining an 80% extraction yield which is lower than the obtained in this research. It is deductible that extending the time process until getting the percentage of total alkaloids extracted for its safe consumption would have demanded greater use of water, time, and energy.…”
Section: Resultsmentioning
confidence: 54%
“…Various studies have been done on the debittering process of L. mutabilis seeds throughout a conventional method (aqueous extraction [AQE]). These studies have been focused on obtaining greater yields or studying the variables that could influence the process (Carvajal‐Larenas, van Boekel, Koziol, Nout, & Linnemann, 2013; Cortés‐Avendaño et al, 2020; Villacrés, Álvarez, & Rosell, 2020); however, this method still is not considered the most efficient due to the high water consumption and long process time, which makes the product more expensive, decreasing its nutritional value and contributing to environmental pollution over the indiscriminate release of alkaloids. As the new tendency in the food industry is obtaining products with high nutritional value, using a sustainable process, characterized for being eco‐friendly, with the minimal generation of toxic residues (Karrar, Sheth, Wei, & Wang, 2019), the supercritical fluid extraction (SFE) has gained increasing acceptance in the industrial sector due to some advantages such as a reduction in costs, time, less toxicity, and environmental acceptance (Mahmood, Daud, Markom, Mansor, & Latif, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The lupin grains were debittered using an aqueous heat processes as previously report (Villacrés et al, 2020a). Briefly, grains were immersed in hot water (80 °C) at a 1:3 ratio (grain:water) for 10 h, then cooked at 91°C for 1 h and finally grains were thoroughly washed at 35 °C for 28 h with continuous changes of water.…”
Section: Grain Debitteringmentioning
confidence: 99%
“…The first limiting amino acids in L. mutabilis are the methionine and cysteine, followed by tryptophan (Table 3). During debittering, besides the removal of quinolizidine alkaloids till safe levels (Villacrés et al, 2020a), there is a concomitant reduction of other nutrients like essential amino acids, principally (methionine, cysteine and tryptophan) (Villacrés et al, 2020b), which are the limiting amino acids in L. mutabilis (Table 3). The fermentation process induced a significant reduction of the tryptophan content (P<0.05) with respect to debittered grain.…”
Section: Effect Of Debittering and Fermentation On The Nutritional Quality Of Lupin Proteinsmentioning
confidence: 99%
See 1 more Smart Citation